Biphasic biocatalysis using a CO2-switchable Pickering emulsion. Issue 15 (29th May 2019) - Yu, Shijie; Zhang, Duyan; Jiang, Jianzhong; Cui, Zhenggang; Xia, Wenshui; Binks, Bernard P.; Yang, Hengquan
Abstract : Biphasic biocatalyses were performed in a CO2 /N2 -switchable Pickering emulsion, in which demulsification and recycling of enzymes can be realized via a N2 /CO2 trigger. Abstract : Biphasic biocatalyses such as the hydrolysis of olive oil and the esterification of octanol with oleic acid were performed in a CO2 /N2 -switchable Pickering oil-in-water emulsion stabilized by silica nanoparticles hydrophobized in situ by a CO2 /N2 -switchable surfactant ( N, N -dimethyldodecylamine). Compared with biphasic systems, the enzyme in the Pickering emulsions displays a higher reaction efficiency, and demulsification and recycling of the enzyme can be simply realized by bubbling with N2 /CO2 . Moreover, the recycled enzyme still possesses significant catalytic activity.